Assessment of Gingival Biotype in the Esthetic Zone among Dental Students at University of Tripoli - Abdullah Otman (AlQalam Journal of Medical and Applied Sciences, 2024)
The form and structure of the soft tissue and maxillary anterior teeth at the esthetic zone play an important role in determining the outcome. The gingival biotype is important because of the structural characteristics of the periodontics. This study targeted to determine gingival biotype prevalence and characteristics in the esthetic zone among Libyan dental students. A cross-sectional study was done for 220 students aged between 20 and 30 years. In the periodontal department, healthy periodontal tissues with no loss of attachment and the presence of all upper anterior teeth were selected. Clinically, gingival biotype was examined and recorded according to the transparency of the periodontal probe and visual inspection. The present study evaluated the frequency of gingival biotype and its association with gender and crown shape. All measurements were made for a total of students according to gingival transparency and were statistically evaluated. This study has shown that gingival biotype varies among different genders, ages, and tooth forms in our population. Understanding tissue biotypes can help dentists choose the correct dental treatment for better results. يلعب شكل وبنية الأنسجة الرخوة والأسنان الأمامية العلوية في المنطقة الجمالية دورًا مهمًا في تحديد النتيجة. يعد النمط اللثوي مهمًا بسبب الخصائص البنيوية لأمراض اللثة. استهدفت هذه الدراسة تحديد انتشار النمط اللثوي وخصائصه في المنطقة الجمالية بين طلاب طب الأسنان الليبيين. أجريت دراسة مقطعية لـ 220 طالبًا تتراوح أعمارهم بين 20 و 30 عامًا. في قسم أمراض اللثة، تم اختيار أنسجة اللثة السليمة بدون فقدان الارتباط ووجود جميع الأسنان الأمامية العلوية. سريريًا، تم فحص النمط اللثوي وتسجيله وفقًا لشفافية مسبار أمراض اللثة والفحص البصري. قيمت الدراسة الحالية تواتر النمط اللثوي وارتباطه بالجنس وشكل التاج. تم إجراء جميع القياسات لإجمالي الطلاب وفقًا لشفافية اللثة وتم تقييمها إحصائيًا. أظهرت هذه الدراسة أن النمط الحيوي للثة يختلف باختلاف الجنسين والأعمار وأشكال الأسنان في مجتمعنا. إن فهم الأنماط الحيوية للأنسجة يمكن أن يساعد أطباء الأسنان في اختيار العلاج السني الصحيح للحصول على نتائج أفضل